Pertumbuhan dan Produksi Buncis Tegak (Phaseolus vulgaris) pada beberapa Kombinasi Media Tanam Organik - Meilya Ramadhiana Safitry; Juang Gema Kartika (Buletin Agrohorti, 2013)
Media selection is one of important factor for the growth and production of erected kidney bean (Phaseolus vulgarisL.). Utilization the waste media of white oyster mushroom (Pleurotus ostreatus) and waste media of paddy straw mushroom (Volvariella volvaceae), cow manure, and rice husk as plant growth media for kidney bean can be used for optimizing the utilization of local resources and minimizing environmental damage as well as to support the codification of GAP (Good Agricultural Practices) of kidney bean. The research was done from February until October 2011 in experiment field at Leuwikopo, IPB, Bogor. The experiment consisted of one factor and arranged in Randomized Complete Design with thirteen combinations from five kinds of organic media component, they were soil, waste media of white oyster mushroom, waste media of paddy straw mushroom, cow manure, and rice husk with 1:1 ratio (v/v). The kidney bean showed good responses to the combination media treatment of cow manure, combination of soil and waste media of paddy straw mushroom, combination of soil, waste media of paddy straw mushroom, and cow manure, and combination of soil, waste media of paddy straw mushroom, cow manure, and rice husk. How ever the best result of kidney bean production was given from waste media of paddy straw mushroom treatment.Keyword:  erected kidney bean, plant growth media, waste media of paddy straw mushroom, co w manure